Bacillus thuringiensis Effect on the Vegetative Development of Cotton Plants and the Biocontrol of Spodoptera frugiperda - Flávia Santana Souza da Costa; Lílian Botelho Praça; Ana Cristina Menezes Mendes Gomes; Roseane Cavalcanti dos Santos; Carlos Marcelo Silveira Soares; Rose Gomes Monnerat (Agronomy, 2020)
Bacillus thuringiensis (Bt) is used worldwide as a tool for controlling lepidopteran pests. Recent studies have demonstrated the possibility of its use as an endophytic organism, controlling insects and promoting plant growth. In this aspect, strains of Bt toxic to lepidopteran pests were inoculated both onto seeds and into cotton plants and were assessed for effectiveness in controlling Spodoptera frugiperda and its effect on promoting plant growth. It was observed that the results obtained from the interaction between the Bt strains (S1450 HD-1, S1905, S2122, S2124) and the cotton genotypes (BRS 8H, BRS Aroeira and BRS 286) showed different growth responses. The results also showed that all the strains may not be suitable to explore the biological control mechanism without undermining plant health. Therefore, the strain S2122, the BRS 8H genotype and seed inoculation were selected to continue the tests by using two concentrations of the bacterium. The results of Bt strain inoculation in seeds and into cotton plants showed that, although plant height, number of leaves, and development stage were influenced by Bt inoculation, overall, there was no significant improvement in the plant growth. The plants that were inoculated with Bt also interfered in the weight of Spodoptera frugiperda, however, did not cause the pest mortality. The collected results suggest that there is a close relationship between the Bt strain and the cotton crop and that colonizing mechanism of the bacterium can be useful in situations that there is an inefficiency of the control measures, since the endophytic Bt makes the pest more susceptible to be controlled by other practices, improving management effectiveness.